2018
DOI: 10.4257/oeco.2018.2203.03
|View full text |Cite
|
Sign up to set email alerts
|

Mamíferos De Médio E Grande Porte No Campus Da Universidade Federal De Lavras, Sul Do Estado De Minas Gerais, Brasil

Abstract: A perda e fragmentação de habitats naturais são as principais causas do declínio da biodiversidade, e mamíferos terrestres de médio e grande porte estão entre os taxa mais afetados por estes processos, pois apresentam baixas taxas de reprodução, grandes áreas de vida e sofrem com a pressão de caça. Neste estudo apresentamos a lista de espécies de mamíferos de médio e grande porte que ocorrem no campus da Universidade Federal de Lavras (UFLA) e comparamos com a fauna da região. O campus da UFLA está localizado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…That is, species that can use different types of habitats and that can be favored in modified landscapes [54]. In addition, some studies have also found no relationship between the richness of medium and largesized mammals and the amount of native habitat [8,21,55,56] or others have recorded a high species richness in landscapes with strong urban [1,58] or agricultural influence [8,49,50]. In this way, species with a wide ecological niche can be favored by these modified landscapes and, probably, maintain their populations in agricultural landscapes [59].…”
Section: Discussionmentioning
confidence: 99%
“…That is, species that can use different types of habitats and that can be favored in modified landscapes [54]. In addition, some studies have also found no relationship between the richness of medium and largesized mammals and the amount of native habitat [8,21,55,56] or others have recorded a high species richness in landscapes with strong urban [1,58] or agricultural influence [8,49,50]. In this way, species with a wide ecological niche can be favored by these modified landscapes and, probably, maintain their populations in agricultural landscapes [59].…”
Section: Discussionmentioning
confidence: 99%
“…In words, landscapes dominated by pastures are predominantly used by generalist species. In addition, some studies have also found no relationship between the richness of medium-and large-sized mammals and the amount of native habitat [8,21,61,62], while others have recorded a high species richness in landscapes with a strong urban [63,64] or agricultural influence [8,44,56]. In this way, species with a wide ecological niche can be favored by these modified landscapes and can, probably, maintain their populations in agricultural landscapes [65].…”
Section: Discussionmentioning
confidence: 99%
“…The medium-sized and large mammals of Atlantic Forest are affected by fragmentation (Ceballos et al 2005, Costa et al 2005, as they have a low reproductive rate, have large home ranges (Cardillo et al 2005, Ceballos et al 2005, Costa et al 2005, Galetti et al 2009, and are subject to hunting (Kasper et al 2007, Araújo et al 2008, Brocardo et al 2012, Brocardo and Cândido-Júnior 2012. Even so, they are still found in many small remnants of seasonal semideciduous Atlantic Forest (Eduardo and , Penido and Zanini 2012, Pires and Cademartori 2012, Magioli et al 2014, Santos et al 2016, Melo-Dias and Passamani 2018.…”
Section: Introductionmentioning
confidence: 99%